The Importance of Aviation Vocational Education in Indonesia - Catra Indra Cahyadi; I Gusti Agung Ayu Mas Oka; Fitri Masito (STAI Hubbulwathan Duri, 2022)
This study aims to analyze the importance of aviation vocational education in Indonesia. This type of research is Research and Development (R D) with a 4D model. However, this research is only limited to the defined stage. This research was conducted in September-October 2021 with the research instrument in the form of a questionnaire. The population taken in this study are all workers in all aviation institutions in Indonesia. From the entire population, a sample of 88 people was then taken. Sampling using a purposive sampling technique. The results of the questionnaire data (questionnaire) were processed using the SPSS application to test the validity and reliability and using excel to obtain the percentage and category of each statement item listed in the questionnaire. The results of this study indicate that aviation vocational education in Indonesia is important.